Communicating quantitative risks and benefits in promotional prescription drug labeling or print advertising. (26th February 2013) - West, Suzanne L.; Squiers, Linda B.; McCormack, Lauren; Southwell, Brian G.; Brouwer, Emily S.; Ashok, Mahima; Lux, Linda; Boudewyns, Vanessa; O'Donoghue, Amie; Sullivan, Helen W.
ABSTRACT Purpose Under the Food, Drug, and Cosmetic Act, all promotional materials for prescription drugs must strike a fair balance in presentation of risks and benefits. How to best present this information is not clear. We sought to determine if the presentation of quantitative risk and benefit information in drug advertising and labeling influences consumers', patients', and clinicians' information processing, knowledge, and behavior by assessing available empirical evidence. Methods We used PubMed for a literature search, limiting to articles published in English from 1990 forward. Two reviewers independently reviewed the titles and abstracts for inclusion, after which we reviewed the full texts to determine if they communicated risk/benefit information either: (i) numerically (e.g., percent) versus non‐numerically (e.g., using text such as "increased risk") or (ii) numerically using different formats (e.g., "25% of patients", "one in four patients", or use of pictographs). We abstracted information from included articles into standardized evidence tables. The research team identified a total of 674 relevant publications, of which 52 met our inclusion criteria. Of these, 37 focused on drugs. Results and conclusions Presenting numeric information appears to improve understanding of risks and benefits relative to non‐numeric presentation; presenting both numeric and non‐numeric information when possible may be best practice. No single specific format or graphical approach emerged as consistently superior. Numeracy and health literacy also deserve more empirical attention as moderators. Copyright © 2013 John Wiley & Sons, Ltd.